Platelet rich plasma concentration improves biologic mesh incorporation and decreases multinucleated giant cells in a dose dependent fashion. (1st October 2021) - Araujo‐Gutierrez, Raquel; Van Eps, Jeffrey L.; Scherba, Jacob C.; Anastasio, Albert Thomas; Cabrera, Fernando; Vatsaas, Cory J.; Youker, Keith; Fernandez Moure, Joseph S.
Abstract: Platelet rich plasma (PRP) has been shown to improve incorporation and reduce inflammation in ventral hernia repair (VHR) with acellular dermal matrix (ADM). The concentration of platelets in PRP varies in clinical studies and an ideal concentration has yet to be defined. The effects of varied concentrations of PRP on ADM incorporation and inflammatory cell infiltration in a rat model of VHR. We hypothesized that increasing concentration of PRP would lead to improved incorporation, decreased CD8+ and multinucleated giant cell (MNGC) infiltrate. Lewis rats underwent ventral hernia creation and repair 30 days later with porcine non‐crosslinked ADM. PRP was applied to the mesh prior to skin closure at concentrations of 1 × 10 4 plt/μL (PRP‐LOW), 1 × 10 6 plt/μL (PRP‐MID), or 1 × 10 7 plt/μL (PRP‐HIGH) and tissue harvested at 2 and 4 weeks. Cellularization, tissue deposition, and mesh thickness using hematoxylin and eosin and Masson's trichrome, and neovascularization was assessed with VVG staining, to establish the relationship of PRP concentration to metrics of incorporation. MNGC and CD8+ T‐cell infiltration were quantified to establish the relationship of inflammatory cell infiltration in response to PRP concentration. Lymphocyte infiltration was assessed using immunohistochemical staining for CD8. PRP‐HIGH treated had significantly greater tissue deposition at 4 weeks. PRP‐MID showed increasing mesh thickness at 2 weeks. Cell infiltration was significantly higher with PRP‐HIGH at both 2 and 4 weeks while PRP‐LOW showed increased cell infiltration only at 4 weeks. At both time points there was a trend towards a dose dependent response in cell infiltration to PRP concentration. Neovascularization was highest with MID‐plt at 2 weeks, yet no significant differences were noted compared to controls. CD8+ cell infiltrate was significantly decreased at 2 and 4 weeks in PRP‐LOW and PRP‐MID treated groups. PRP at all concentrations significantly decreased MNGC infiltration at 2 weeks while only PRP‐HIGH and PRP‐MID had significant reductions in MNGC at 4 weeks. Both MNGC and CD8+ cell infiltration demonstrated dose dependent reduction in relation to PRP concentration. Increasing platelet concentrations of PRP correlated with improved incorporation, tissue deposition, and decreased scaffold degradation. These findings were associated with a blunted foreign body response. These findings suggest PRP reduces inflammation which may be beneficial for ADM incorporation in VHR.